Electrophysiological correlates of predictive coding of auditory location in the perception of natural audiovisual events - Stekelenburg, Jeroen; Vroomen, Jean (Frontiers in Integrative Neuroscience, 2012)
In many natural audiovisual events (e.g., a clap of the two hands), the visual signal precedes the sound and thus allows observers to predict when, where, and which sound will occur. Previous studies have already reported that there are distinct neural correlates of temporal (when) versus phonetic/semantic (which) content on audiovisual integration. Here we examined the effect of visual prediction of auditory location (where) in audiovisual biological motion stimuli by varying the spatial congruency between the auditory and visual part of the audiovisual stimulus. Visual stimuli were presented centrally, whereas auditory stimuli were presented either centrally or at 90° azimuth. Typical subadditive amplitude reductions (AV – V < A) were found for the auditory N1 and P2 for spatially congruent and incongruent conditions. The new finding is that the N1 suppression was larger for spatially congruent stimuli. A very early audiovisual interaction was also found at 30-50 ms in the spatially congruent condition, while no effect of congruency was found on the suppression of the P2. This indicates that visual prediction of auditory location can be coded very early in auditory processing.